Covid-19 Bantu Lingkungan Bangkit Kembali Dari Pandemi Menuju Pembangunan Berkelanjutan - Muliaty Galib (Universitas Jambi, 2022)
ABSTRACT The Covid-19 pandemic has become a historic momentum for the entire world which has almost weakened the entire wheel life. However, it does not weaken the determination to always try to improve a better life. Indonesia is a developing country making a pandemic a positive thing in realizing its goals sustainable development (Sustainable Development Goals / SDGs). The Sustainable Development Goals and Covid-19, reports that of the 17 SDGs goals, Indonesia has been able to realize the 10 existing goals, between other sustainable urban and community improvement, terrestrial and marine ecosystems, gender equality, partnerships to achieve goals. Covid-19 becomes an opportunity for the earth as well as to buildblue sky jernihand clear the air. During times of worldwide lockdown, the view of the blue sky creates a feeling community optimist for a cleaner and better environment. According to Arora et al. (2020) says that